(untitled) (Journal of Philosophy Culture and Political Science, 2025)
This article provides a bibliographic review of works by Turkestan scholars from the Kazakh steppe preserved in Turkish archives and libraries, evaluating each scholar’s contribution to science and culture. The discussion section highlights scholars associated with Turkestan. This facilitates the introduction of our cultural heritage into scientific discourse and exemplifies the continuity of scientific and educational traditions among Turkic peoples. Thus, efforts were made to examine the cultural heritage of the Eastern Turkic world as a phenomenon. To achieve this goal, the methodology proposed by C. Mace (2015) was implemented step-by-step in working with manuscripts: collecting manuscripts, compiling manuscript lists in catalogs, providing complete manuscript descriptions, comparing manuscripts, reviewing manuscripts, and analyzing texts. The Turkish manuscript portal was used to examine the manuscripts. The article focuses on Turkestan scholars who contributed to the development of culture and science, examining the collections of Suleymaniye, Milli, Millet, and Kastamonu libraries where their works are preserved. Since independence, the study of the cultural heritage of scholars from Kazakh lands has been actively pursued. This topic has its own challenges, research questions, and directions. In particular, our article thoroughly examines the specifics of searching for scholars by city and region names. As a result, we concluded that domestic researchers have not yet reached sufficient levels in comprehensively covering and deeply analyzing the works of scholars from Kazakh lands. This indicates the need to methodologically improve the research of Turkestan scholars’ heritage in their homeland Kazakhstan and determine its place in world culture. Keywords: scholars of Kazakh lands, Khoja Ahmed Yasawi, Ahmed Yugneki, Hibatullah Tarazi, Turkistanis, Suleymaniye Library, Turkic scholars, phenomenon of cultural heritage of the eastern Turkic world, biobibliography.